2019
DOI: 10.3390/catal9040306
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of New ZrNi5/Nb2O5 Catalytic Agent on Storage Behavior of Nanocrystalline MgH2 Powders

Abstract: Due to its availability and high storage capacity, Mg is an ideal material in hydrogen storage applications. In practice, doping Mg/MgH2 with catalyst(s) is necessary in enhancing the de/rehydrogenation kinetics and minimizing both of decomposition temperature and its related apparent activation energy. The present study proposed a new heterogeneous catalytic agent that consisted of intermetallic compound (ZrNi5)/metal oxide (Nb2O5) binary system for using with different concentrations (5−30 wt%) to improve Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Shimadzu Thermal Analysis System/TA-60WS, Saitama, Japan, using normal differential scanning calorimeter (DSC) was employed to investigate the decomposition temperatures of MgH 2 powders with a heating rate of 5 • C/min. The apparent activation energy of decomposition (E a ) for the powders obtained after different RBM time were investigated, using the Arrhenius approach with different heating rates (5,10,20,30,40 • C/min).…”
Section: Normal Dscmentioning
confidence: 99%
See 2 more Smart Citations
“…Shimadzu Thermal Analysis System/TA-60WS, Saitama, Japan, using normal differential scanning calorimeter (DSC) was employed to investigate the decomposition temperatures of MgH 2 powders with a heating rate of 5 • C/min. The apparent activation energy of decomposition (E a ) for the powders obtained after different RBM time were investigated, using the Arrhenius approach with different heating rates (5,10,20,30,40 • C/min).…”
Section: Normal Dscmentioning
confidence: 99%
“…Reactive ball milling (RBM), which was investigated in the beginning of the 1990s [1,2] is a cost effective process, employed for conducting gas-solid reactions at ambient temperature, starting from pure metal and desired gas. Since then, RBM has been intensively used to produce large amounts of high quality MgH 2 nanocrystalline powders, starting from Mg metal and hydrogen gas [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our previous work reported that Mo oxide The niobium pentoxide exists in several structures with the polymorphs mostly being derived from the ReO 3 type structure. The main phase for Nb 2 O 5 occurs upon calcination of the amorphous niobium oxide in the 600-800 • C range with predominance of orthorhombic structure e.g., T-Nb 2 O 5 while the pseudohexagonal one, e.g., TT-Nb 2 O 5 is observed at lower temperatures [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It takes 425 s to absorb 6.2 wt % H 2 at 200 °C and 3 MPa, and 700 s to dehydrogenate 6.2 wt % H 2 at 225 °C. The research team also developed ZrNi 5 /Nb 2 O 5 [22b] and Zr 70 Ni 20 Pd 10 [22c] alloy catalysts, which not only have faster hydrogen absorption and desorption properties (Zr 70 Ni 20 Pd 10 can release 6 wt % H 2 within 3.8 min at 200 °C), but also maintain a good hydrogen storage capacity over hundreds of cycles. L.T.…”
Section: Catalyst Dopingmentioning
confidence: 99%